Evaluating the performance of WRF-CMAQ air quality modelling system in Bulgaria by means of the DELTA tool. (2015) - Georgieva, Emilia; Syrakov, Dimiter; Prodanova, Maria; Etropolska, Iglika; Slavov, Kiril
Model evaluation is performed based on comparison of simulated and observed air pollution concentrations at 25 background stations of the Bulgarian national air quality monitoring network for the year 2013. The DELTA software package, developed within the forum for air quality modelling in Europe - FAIRMODE, is used to analyse model results focusing on maximum daily eight-hour mean ozone concentrations, hourly nitrogen dioxide (NO2 ) and daily particulate matter (PM10 ) concentrations. Ozone is overestimated by 38%, minimum daily values are overestimated by a factor of 3. NO2 and PM10 are underestimated by a factor of, respectively, 4 and (5 to 9). The main DELTA model quality objective is respected at 26% of the stations for ozone, 58% of the stations for NO2, and nowhere for PM10 . The best model performance is for ozone at rural sites during summer. Possible ways for improvement of model results are discussed.